Pengaruh Elemen Ekuitas Merek Terhadap Rasa Percaya Diri Pelanggan Dan Keputusan Pembelian Hijab - Rahmi Fauziyawati; Lila Dini Utami (Universitas Bina Sarana Informatika, 2016)
In the mid-90s there were very rare muslim fashion boutiques. However, at that time many people knew muslim fashion boutiques. As for the muslin dress boutique Zoya, a brand transformation results from Rumah Kerudung and dress Veil Lamara containing a wide variety of brands with the concept of house of brand. The characteristic of product design is fashion Zoya's simple and interesting. The brand can be interpreted as a name representing the product as a whole. Brand equity is the value given on the product and services. Customer awareness of the quality of a brand, showed the presence of the brand uniqueness compared to other brands. This causes customers have reason to buy these brands (reason to buy) and have an impact on the incidence of confidence over the purchase decision. This study analyzes the influence of the elements of the brand equity Of the confidence The Customers purchasing decision hijab Zoya. This research uses a multiple linear regression analysis to assess the effects of brand equity and confidence towards hijab purchasing decision Zoya. As a result, brand equity and beliefs affect the purchasing decision hijab Zoya. Variable beliefs have a dominant influence on purchasing decisions.